Electrosynthesis Metal-Organic Frameworks (MOFs) Cu-BDC Using Ionic Liquid by Anodic Dissolution Method - Ibrahim, Andy
In this research, Cu-BDC (cuprum(II)-1,4-benzenedicarboxylate) MOFs (metal-organic frameworks) has been synthesized by electrolysis method. This synthesis was conducted under anode dissolution technique by applying a constant voltage. Structure and crystallinity of Cu-BDC MOFs were investigated by means of PXRD (Powder X-Ray Diffraction), decomposition reaction were studied by using TGA (Thermogravimetric Analysis), the related chemical functional group of Cu-BDC were examined with FTIR spectroscopy (Fourier-Transform Infra Red), morfology and particle size obtained from SEM (Scanning Electron Microscopy). Electrosynthesis profiles showed that the increasing of the applied voltage was in line with the increasing of the rate of the oxidation at anode. In the other side, the electrochemical current decreased as a function of time. PXRD results indicate that the characteristic peaks of Cu-BDC MOFs at 2? equal to 10,4°;17,12°;24,79° appeared with good cristallinity. FTIR result indicates the coordinating bond between the BDC2- ligand with the metal ion Cu2+. TGA showed that the decomposition temperature 5V and 10V electrosynthesized Cu-BDC stable up to to 325 °C while 15V electrosynthesized Cu-BDC stable up to 275°C. From the results of the SEM showed that the crystals obtained from electrosynthesis Cu-BDC has polycrystalline morphology which has particle size of 50-500 nm. The optimum conditions to obtain Cu-BDC with a relatively short time synthesis and with good results is in the voltage of 10V.